Aplikasi Konsultasi Psikologi Berbasis Flutter dan ChatGPT Menggunakan Metode Extreme Programming - Yuniarti, Anisa; Munir, Sirojul; Asqia, Misna (LPPM STT Terpadu Nurul Fikri, 2025)
This study explores the development of a psychology consultation application built on Flutter, incorporating ChatGPT API integration to address the need for easily accessible mental health services, particularly during the COVID-19 pandemic. The main issue addressed is the limited access to quick and efficient psychological support. The application provides features such as user registration, psychologist search, appointment scheduling, and an AI chatbot for immediate assistance. The Extreme Programming (XP) method was employed in the application development, utilising Flutter for building the interface and the ChatGPT API for chatbot integration. The development process included system design, implementation, and evaluation. The results indicate that the application is practical in providing easily accessible psychological consultation services. Black Box testing showed a success rate of 90%, while User Acceptance Testing (UAT), with 15 participants, showed a satisfaction rate of 88%. The questionnaire results indicated that all users agreed that the application facilitated access to psychological consultation services, with positive feedback on the ease of use and effectiveness of the features. For future development, the focus should be on enhancing the application's functionality to improve the overall user experience and meet the standards of an effective and efficient application.